Implementing a Swedish regionalized medical program supported by digital technologies: possibilities and challenges from a management perspective - Pettersson, Fanny (Rural and remote health, 2013)
In 2011, Umeå University in Sweden was facing its first attempt to transform the existing medical program into a regionalized medical program (RMP), supported by the use of digital technologies. The Swedish RMP means that students are distributed in geographically separated groups while doing their five clinical clerkship semesters. To provide medical students with ways of undertaking their theoretical studies when geographically distributed, digital technologies are used for educational and administrative purposes. In this article, the Swedish RMP will be described and related to previous international research on educating medical students in rural settings. The aim of this article was, from a management perspective, to understand if and how contradictions arise during the implementation process of the Swedish RMP, supported by digital technologies. Based on this analysis, a further aim was to discuss, from a management perspective, the possibilities and challenges for improvement of this medical educational practice, as well as to provide implications for other similar changes in medical programs internationally. To identify possible contradictions during the implementation process, ethnographically inspired observations were made during management work meetings, before and during the first regionalized semester. In addition, in-depth follow-up interviews were held in May and June 2011 with six management executives of the Swedish RMP, concerning their expectations and experiences of the implementation process. The qualitative and activity theory (AT)-inspired analysis resulted in the emergence of two main themes and seven sub-themes. The analysis suggests that a number of contradictions arose during the implementation process of the Swedish RMP. For instance, a contradiction constituted as a conflict between the university management and some teachers concerning how digital technologies and technology enhanced learning (TEL) could and should be used when educating medical students. In addition, due to the use of digital technologies the implementation process helped to reveal existing problems and tensions in educational practice, not previously visible to management. These included contradictions such as a lack of alignment in how course goals, teaching practices, and examinations should be carried out. Further, obsolete course content and overlap between courses and subjects were identified, leading to an overhaul of all semesters, not only those regionalized. This study showed how contradictions in educational practice arose when the Swedish RMP, supported by digital technologies, was implemented. These contradictions involve both possibilities and challenges for management to improve how and with what quality the Swedish RMP is conducted. A challenge for management is to find the most effective way to enhance up-take and use of the more interactive and innovative TEL-solutions. However, a possibility is that the regionalization process and implemented improvements may also influence non-regionalized semesters, with the potential to eventually increase the quality of the entire program.